KUR Credit Scoring Assessment for Prospective Debtors to Minimize Non-Performing Loans at BPD South Sumatra Babel Main Branch Captain A.Rivai - Divaputri, Adelya; Panuntun, Bagus (Journal Of Accounting Management Business And International Research, 2025)
The research entitled "KUR Credit Scoring Assessment Procedure for Prospective Debtors to Minimize Non-Performing Loans at the Regional Development Bank of South Sumatra Babel, Captain A.Rivai Main Branch" analyzes the credit scoring process that occurs at Bank Sumsel Babel. The main focus of the research is understanding the obstacles in credit scoring assessment. The research method used is descriptive qualitative research in the form of observation, interviews and documentation. Recommendations for Bank Sumsel Babel Main Branch Captain A.Rivai Palembang include improving the assessment form in the form of adding question points on the credit analysis worksheet to developing a device or system in the form of an integrated platform/website.